Anti-Acne Vulgaris Potential of the Ethanolic Extract of Mesua ferrea L. Flowers - Wongnapa Nakyai; Wachirachai Pabuprapap; Wichuda Sroimee; Vachiraporn Ajavakom; Boon-ek Yingyongnarongkul; Apichart Suksamrarn (Cosmetics, 2021)
Acne vulgaris is a common chronic inflammatory skin disease. In the present study, we reported the anti-acne vulgaris effect of the Mesua ferrea (M. ferrea) flower extract. The extract was evaluated for three anti-acne-causing bacteria properties including Cutibacterium acnes (C. acnes), Staphylococcus epidermidis (S. epidermidis) and Staphylococcus aureus (S. aureus). The results indicated that the M. ferrea flower extract could be considered as the bactericidal agent against S. epidermidis and S. aureus with MIC values of 0.78 and 6.25 mg mL−1 and MBC values of 1.56 and 12.50 mg mL−1 and the bacteriostatic agent against C. acnes with MIC and MBC values of 3.12 and 25.00 mg mL−1, respectively. The extract at a concentration of 25 µg mL−1 also presented potent anti-inflammatory activity with a significant decrease of nitric oxide (NO) and tumor necrosis factor (TNF)-α productions in RAW 264.7 macrophage cells stimulated by LPS. In addition, the extract showed moderate to weak anti-oxidative capacities against DPPH, ABTS, FRAP and NO assays and also showed weak anti-tyrosinase activity. M. ferrea flower extract may serve as the alternative natural anti-acne formulations.